Barrier Capacity of Human Placenta for Nanosized Materials - Wick, Peter (National Institute of Environmental Health Sciences, 2010)
BACKGROUND: Humans have been exposed to fine and ultrafine particles throughout their history. Since the Industrial Revolution, sources, doses, and types of nanoparticles have changed dramatically. In the last decade, the rapidly developing field of nanotechnology has led to an increase of engineered nanoparticles with novel physical and chemical properties. Regardless of whether this exposure is unintended or not, a careful assessment of possible adverse effects is needed. A large number of projects have been carried out to assess the consequences of combustion-derived or engineered nanoparticle exposure on human health. In recent years there has been a growing concern about the possible health influence of exposure to air pollutants during pregnancy, hence an implicit concern about potential risk for nanoparticle exposure in utero. Previous work has not addressed the question of whether nanoparticles may cross the placenta. OBJECTIVE: In this study we investigated whether particles can cross the placental barrier and affect the fetus. METHODS: We used the ex vivo human placental perfusion model to investigate whether nanoparticles can cross this barrier and whether this process is size dependent. Fluorescently labeled polystyrene beads with diameters of 50, 80, 240, and 500 nm were chosen as model particles. RESULTS: We showed that fluorescent polystyrene particles with diameter up to 240 nm were taken up by the placenta and were able to cross the placental barrier without affecting the viability of the placental explant. CONCLUSIONS: The findings suggest that nanomaterials have the potential for transplacental transfer and underscore the need for further nanotoxicologic studies on this important organ system.